Weaving into public policy, the right to education of excombatant women (2017)
The purpose of this article is to explore and identify a series of strategies and / or guidelines that can be considered in the elaboration of public educational policies aimed at ex-combatant women linked to disarmament, reintegration and reintegration processes - DDR. For this, the concepts referring to gender approach and right to education will be addressed, analyzing the pros and cons of its application within the framework of the Peace Agreement signed by the National Government and the Revolutionary Armed Forces of Colombia - FARC, taking into account the recommendations from the international community, some public institutions, researchers and ex-combatants, who have been in charge of studying previous processes.